PHYSICO-CHEMICAL PARAMETERS OF RAM GANGA RIVER IN PITHORAGARH, UTTARAKHAND (INDIA) - SINGH, C. P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2019)
Present investigation has been carried out on the various physico-chemical parameters such as temperature, pH, dissolved oxygen, free co2 and BOD of Ram Ganga River district Pithoragarh Uttarakhand (India). The pH was recorded in the range of 7.0 - 8.2. The water temperature was recorded range 14C – 26C. Free CO2 of water sample range 1.2 to 2.5 mg/l. Chloride range between 13.5 – 21.6 mg/l. Turbidity range between 1 to 3.5 mg/l. The BOD range 2.1 to 4.6 mg/l. Present study these Physico-chemical parameters are necessary for judging the suitable for water or attributed to growth death and decay of phytoplankton.